320Applying novel multi-disciplinary methodologies to accelerate malaria elimination. (2nd September 2021) - Agius, Paul; Simpson, Julie; Dini, Saber; Gething, Peter; Devine, Angela; Fowkes, Freya
Abstract: Focus and outcomes for participants: Presented by researchers from the Australian Centre of Research Excellence in Malaria Elimination (ACREME, www.acreme.org.au), the focus of the symposium will be the application of multi-disciplinary epidemiological and statistical approaches to inform the control and elimination of malaria in the Asia-Pacific region. The epidemiology of malaria is complex as it involves multiple mosquito vectors, different malarial species (that require species-specific treatments) and emerging insecticide and antimalarial drug resistance. The symposium will provide an overview of the significance of the changing epidemiological landscape of malaria globally, and how modern epidemiological methods, such as stepped-wedge designs, multi-state modelling, within-host mechanistic mathematical models, geospatial methods and cost-effectiveness modelling applied to clinical effectiveness trials, prospective cohort studies, volunteer infection studies and national and regional data have contributed to answering the key challenges in malaria research. Specifically we will discuss evidence for effective interventions to reduce the risk of malaria transmission, the effect of recurrent episodes of malaria on risk of hospitalisation and mortality, the selection of antimalarial drug combination therapies to fast track new drugs, understanding geospatial heterogeneity of malaria transmission, and the cost-effectiveness of scenarios using different treatment regimens. Discussion of the importance of these methodologies and their findings will be contextualised in the current global malaria elimination goals. As similar transformations in epidemiological environment have occurred in other disease elimination settings, we believe this symposium will have broad appeal and that the challenges faced and the methodological solutions proposed to accelerate progress in malaria elimination will have a high degree of relevance and be useful to researchers working in global health or infectious diseases. Rationale for the symposium, including for its inclusion in the Congress: Following a two-decade period of declining malaria burden due to intensified control efforts, global progress against the disease has stalled, and in some countries, malaria has resurged. Emerging parasite resistance to insecticides and antimalarial drugs has reduced the effectiveness of cornerstone malaria control interventions. Malaria endemic areas of the Greater Mekong Sub region (GMS) have set the target to eliminate malaria by 2030, however, the failure of these established interventions and transition to low-transmission endemic environments has necessitated fundamental re-evaluation of the epidemiological landscape of the disease and emphasised timely development of robust evidence for novel interventions. In order to provide evidence, a wide range of advanced multi-disciplinary methodologies have been developed and applied in many malaria epidemiology areas and we believe discussion of these in the symposium will be highly relevant given the principal theme of the 2020 WCE (Methodological Innovations in Epidemiology). Additionally, the symposium will feature research where findings have been effectively translated to national and regional policy and practice, an important theme of the 2020 WCE. Presentation program: Pragmatic randomised controlled trials (RCT) for population interventions in combating malaria infection Multistate modelling to investigate the impact of recurrent malaria episodes on hospital admissions and mortality Mechanistic within-host modelling to fast-track the selection of new antimalarial combination therapies Geospatial modelling to characterise spatial heterogeneity in malaria transmission and efficiently target areas of high burden Modelling the cost-effectiveness of strategies for malaria patient management to inform public health policy Names of presenters: Mr. Paul Agius, Senior Research Fellow, Burnet Institute, Melbourne, Victoria, Australia Professor Julie Simpson, Head of Biostatistics Unit, Centre for Epidemiology and Biostatistics, Melbourne School of Population and Global Health, The University of Melbourne, Melbourne, Victoria, Australia Dr. Saber Dini, Research Fellow, Centre for Epidemiology and Biostatistics, Melbourne School of Population and Global Health, The University of Melbourne, Melbourne, Victoria, Australia Professor Peter Gething, Professor in Epidemiology, Telthon Kids Institute, Perth, Western Australia, Australia Dr. Angela Devine, Senior Research Officer, Division of Global and Tropical Health, Menzies School of Health Research, Charles Darwin University, Darwin, Northern Territory, Australia